Intention to adopt Cloud-based e-Learning in Nigerian Educational Institutions - Tom, A M; Virgiyanti, W (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
Institutions of higher education must utilize innovative information and communication technologies for teaching in Nigeria. Thus, cloud-based e-Learning is essential to curtail educational challenges such as limited infrastructure, funds, and student-to-lecturer ratio. Recently, there has been widespread enthusiasm regarding Cloud computing for e-Learning; adopting and strategically utilizing these technologies remains a significant challenge for higher education institutions. Furthermore, there is a limited understanding of how cloud-based e-learning can transform Nigerian educational establishments. Cloud-based e-Learning systems' technological components have been the subject of numerous study studies, but little is known about how they operate from an organizational perspective. Accordingly, using the Technology-Organization-Environment theory, the goal of this study is to investigate the variables that influence the adoption of cloud-based e-learning. The findings of the research show that relative benefit and competing pressure have a big impact on whether cloud-based e-learning is adopted. However, compatibility, security, and top management commitment do not appear to be significant determinants. These findings will help Nigerian education institutions, the ministry of education, and practitioners to understand the critical factors for adopting this technology for improved education.